Nutrition, stress, and healthcare use during pregnancy are associated with low birth weight: evidence from a case–control study in West Ethiopia - Feyisa, Bikila Regassa; Mulatu, Yosef; Fentahun, Firehiwot; Biru, Bayise; Atlantis, Evan (Frontiers in Public Health, 2023)
Background: Low Birth Weight (LBW) remains a major public health concern globally, especially in lower and middle-income countries. In Ethiopia in general and in the study area in particular there is limited evidence regarding maternal factors associated with low birth weight. This study aimed to identify the maternal factors associated with low birth weight among neonates born in public health facilities in the west Wollega zone, West Ethiopia.We used a case-control study design and selected participant mothers with a newborn using the delivery database from three public hospitals and five health centers, between March 2022 and April 2022. Cases were identified using a newborn birth weight of <2,500 grams. Controls were identified using a newborn birth weight of ≥2,500 grams. An interviewer-administered structured questionnaire and chart review were used for data collection. Model fitness was assessed by Hosmer and Lemenshow goodness-of-fit test, including multi-collinearity checks. Candidate predictor variables were selected (using a pvalue <0.25 in bivariable logistic regression models) for multivariable logistic regression to quantify the association between independent variables and LBW, expressed using Odds Ratios (OR) with a 95% Confidence Interval (CI). Mean and Standard Deviation (SD), all such values.Results: A total of 324 mothers with their newborns (81 cases and 243 controls) were eligible for inclusion. The mean age of participants was 27.9 years (SD 6.4) in cases and 25 years (SD 3.9) in controls. Mean birth weight was 2,128 grams (SD 1,697) in cases and 2,988 grams (SD 378) in controls. In multivariable logistic regression analysis, lack of nutritional counseling (OR=2.4; 95%CI: 1.24-4.72), maternal middle upper arm circumference of <23 cm (OR= 3.1; 95%CI: 1.64-5.91), maternal stress during pregnancy (OR=2.8; 95% CI:1.23-6.36), and antenatal follow up less than four visits (OR=2.8; 95% CI: 1.12 -6.82) were independently associated with LBW.In this study, lack of nutritional counseling, maternal undernutrition, maternal stress during pregnancy, and antenatal follow-up visits less than recommended were associated with LBW. Special attention should be given to promoting antenatal care and counseling mothers on nutrition and relaxation to prevent stress during pregnancy.